Metabolism and pharmacokinetics studies of allyl methyl disulfide in rats. (2nd January 2019) - Liu, Yan; Li, Ang; Jiang, Xiaoyan; Zhu, Xiaosong; Feng, Xiuli; Sun, Xiao; Zhao, Zhongxi
Abstract: 1. Allyl methyl disulfide (AMDS) is one of the main compounds in garlic, whereas its metabolism has not been studied yet. 2. In this work, we first identified the metabolites of AMDS in rat erythrocytes and rats using GC–MS. The transformation mechanism study among different metabolites was then conducted. The apparent kinetics of AMDS in rat erythrocytes and pharmacokinetics of AMDS by oral administration in rats were also studied. 3. The metabolic pathway study showed that AMDS was mainly metabolized in rats to allyl methyl sulfoxide (AMSO) and allyl methyl sulfone (AMSO2 ) through mechanisms of reduction, methylation and oxidation. The transformation mechanism study indicated that AMDS was firstly reduced to allyl mercaptan (AM) in rat erythrocytes, and then methylated to allyl methyl sulfide (AMS) by S-adenosylmethionine (SAM) and S-adenosylhomocysteine (SAH), and finally oxidized to AMSO and AMSO2 by liver microsomes. The half-life of AMDS in rat erythrocytes was 6.285 ± 0.014 min while the half-lives of its active metabolites AMSO and AMSO2 in vivo were 18.17 and 17.50 h, respectively. Also, the large AUCs of the two active metabolites were observed, indicating potential applications of AMDS for certain pharmacological effects.